Laporan geran penyelidikan Mosti E-Science Scf-0065-Bio-2009 "Quorum sensing antagonists in dietary plants" - Zarina Amin; Vijay Kumar Subbiah; Roslinah Hussein; Ruzaidi Ali Mukhtar (Universiti Malaysia Sabah, 2011)
No Abstract